Model Komunikasi Kelompok Pada Organisasi English Lover Santri - Moch. Doni Fadilah; Mokhammad Baharun (Fakultas Dakwah Universitas Ibrahimy, 2022)
There is an interesting study group at the Salafiyah Syafi’iyah Islamic Boarding School Sukorejo, namely the English Lover Organization. One of the things that makes him interested is the communication model in conducting learning discussions. The purpose of this study was to determine the model of group communication in the English Lover Santri Salafiyah Syafi’iyah Sukorejo Organization. The method used in this research is a qualitative research method with a case study research model. The results of this study are that the group communication model in the English Lover Santri Salafiyah Syafi’iyah Sukorejo Organization takes place effectively. There is a stimulus and response from each individual in the group so as to produce a source of information that can be communicated from a set of communicated messages, and with the similarity of experience from the source and target of communication it feels more productive. So that survival in the organization goes in accordance with the existing vision and mission.